Remodeling of Cancellous and Cortical Canine Bone in Response to Decreased Mechanical Loading - Kamibayashi, L.; Pfeiffer, S.; Hearn, T.; Taves, C.; Thomason, J. J.; Binnington, A. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1989)
Thirteen pairs of tibiae were excised from adult mongrel dogs following a mean recovery period of 24.2 weeks after unilateral total hip arthroplasty (THA). Prior to euthanasia, peak vertical dynamic load, as a percent of body weight, was determined for each limb at a walking pace. Four contiguous proximal sections and one transverse cortical midshaft section, 5mm thick, were harvested from each tibia. Contact Faxitron radiographs of the sections were quantified, using video digitizing software, to compare mean apparent density measures between the treated (THA) and intact limbs. There was a significant difference in mean apparent density of cancellous bone with the treated limb having a lower apparent density than the intact limb. The mean cortical area at the midshaft was significantly lower and the medullary area significantly higher among tibiae from the treated side, as compared to the contra-lateral tibiae. Resistance to bending and tension at the midshaft of each bone were determined using the second moment of area about cranio-caudal (Ix) and mediolateral (Iy) axes. The mean Iy values for the treated limbs were significantly lower than for the intact limbs. Therefore, measurable adaptive bone remodeling appears to be present in both cancellous and cortical bone in the tibia due to decreased mechanical loading.
Keywords: Osteopenia; Osteoporosis; Gait; Canine model